2015
DOI: 10.1080/15592294.2015.1042646
|View full text |Cite
|
Sign up to set email alerts
|

An aromatic cage is required but not sufficient for binding of Tudor domains of the Polycomblike protein family to H3K36me3

Abstract: Polycomblike (Pcl) proteins are important transcriptional regulators and components of the Polycomb Repressive Complex 2 (PRC2). The Tudor domains of human homologs PHF1 and PHF19 have been found to recognize trimethylated lysine 36 of histone H3 (H3K36me3); however, the biological role of Tudor domains of other Pcl proteins remains poorly understood. Here, we characterize the molecular basis underlying histone binding activities of the Tudor domains of the Pcl family. In contrast to a predominant view, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Interestingly, the binding affinity of MTF2 to an H3K36me3 peptide is much lower than that of PHF1 due to loss of a key aromatic residue ( Fig. 5A; Gatchalian et al 2015;Li et al 2017). Thus, while all PCLs stimulate PRC2 activity, we speculate that MTF2 mediates PRC2 recruitment to sites devoid of H3K36me2/me3, while PHF1 and PHF19 stabilize PRC2 on sites occupied by H3K36me2/me3.…”
Section: Features Of the Prc2 Holoenzyme Regulated By Distinct Accessmentioning
confidence: 88%
“…Interestingly, the binding affinity of MTF2 to an H3K36me3 peptide is much lower than that of PHF1 due to loss of a key aromatic residue ( Fig. 5A; Gatchalian et al 2015;Li et al 2017). Thus, while all PCLs stimulate PRC2 activity, we speculate that MTF2 mediates PRC2 recruitment to sites devoid of H3K36me2/me3, while PHF1 and PHF19 stabilize PRC2 on sites occupied by H3K36me2/me3.…”
Section: Features Of the Prc2 Holoenzyme Regulated By Distinct Accessmentioning
confidence: 88%
“…Ser86 in MTF2 takes the place of an aromatic residue, which is Phe71 in PHF1 or Tyr80 in PHF19, respectively ( Figure 1G). This incomplete aromatic cage might cause the weaker binding ability of H3tK27me3, like that of H3K36me3 (Gatchalian et al, 2015). Indeed, mutating Ser86 of MTF2 to phenylalanine or tyrosine resulted in dramatically enhanced binding affinities (Table 1).…”
Section: Tudor Domains Of Phf1 and Phf19 Preferentially Bind To Testimentioning
confidence: 99%
“…We have previously shown that the complete aromatic cage in the Tudor domain of Drosophila Pcl is necessary but insufficient for binding to H3K36me3 and that the adjacent hydrophobic patch is also required 26 . The fact that we were unable to generate the gain-of-function mutant of Set4 by engineering the Set3-like aromatic cage suggests that other surface residues play an imperative role.…”
Section: Resultsmentioning
confidence: 99%